2014
DOI: 10.5942/jawwa.2014.106.0106
|View full text |Cite
|
Sign up to set email alerts
|

Application of photoelectrochemical chemical oxygen demand to drinking water

Abstract: MATERIALS AND METHODSModel compound preparation. Three amino acids (tyrosine, tryptophan, phenylalanine), three carboxylic acids (sodium acetate, sodium oxalate, and sodium formate), and two reference standards (potassium hydrogen phthalate [KHP] and caffeine) were used as model organic compounds. These model organic compounds are summarized in Table 1.Carboxylic acids and amino acids are found in natural waters and can make up 8% and 2-3% of COD in natural waters, respectively (Langlais et al, 1991). Relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
14
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 18 publications
3
14
2
Order By: Relevance
“…As anthracite media is not recognized for its adsorptive capacity, substrate could be available to the biomass as hydrophilic organic material that was not adsorbed to alum floc during coagulation. Stoddart and Gagnon (2014) demonstrated that TOC and DOC had the same concentration following biofiltration at this plant, which indicates that organic material enmeshed in floc material was physically removed. However, the photoelectrochemical chemical oxygen demand concentration was decreased following coagulation/flocculation (adsorption) and then further decreased through biofiltation (biodegradation) (Stoddart & Gagnon 2014).…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…As anthracite media is not recognized for its adsorptive capacity, substrate could be available to the biomass as hydrophilic organic material that was not adsorbed to alum floc during coagulation. Stoddart and Gagnon (2014) demonstrated that TOC and DOC had the same concentration following biofiltration at this plant, which indicates that organic material enmeshed in floc material was physically removed. However, the photoelectrochemical chemical oxygen demand concentration was decreased following coagulation/flocculation (adsorption) and then further decreased through biofiltation (biodegradation) (Stoddart & Gagnon 2014).…”
Section: Resultsmentioning
confidence: 68%
“…Stoddart and Gagnon (2014) demonstrated that TOC and DOC had the same concentration following biofiltration at this plant, which indicates that organic material enmeshed in floc material was physically removed. However, the photoelectrochemical chemical oxygen demand concentration was decreased following coagulation/flocculation (adsorption) and then further decreased through biofiltation (biodegradation) (Stoddart & Gagnon 2014). For Atlantic Canada surface water, hydrophilic acids are significant contributors to haloacetic acid (HAA) formation (Kent et al 2014) and during biofilter operation at this facility, the degradation of HAA precursors was evident (Stoddart & Gagnon 2015).…”
Section: Resultsmentioning
confidence: 68%
“…This is consistent with a recent finding in which, using data from several pilot-and full-scale studies, no correlation between ATP concentrations and DOC removal was identified (Pharand et al 2014). However, as described in Stoddart and Gagnon (2014), additional data from this facility indicate that a 0.26 mg/L DOC reduction across the biofilter can correspond to a 1.5 mg/L removal of oxidizable organic matter (as measured through photoelectrochemical chemical oxygen demand) across the filter. As a result, it is hypothesized that more biological transformation of NOM may occur than is detectable by DOC.…”
Section: Resultsmentioning
confidence: 77%
“…Combining chemical oxygen demand (COD) with TOC/DOC measurement can provide valuable information on the oxidation state of organic carbon during drinking water treatment. However, the conventional dichromate COD method is not sensitive enough to measure COD in surface water (Rittman & Huck, 1989;Stoddart & Gagnon, 2014). Advancements in sensor development for the determination of COD in water have allowed researchers to rapidly quantify COD during drinking water treatment using photoelectrochemical chemical oxygen demand (peCOD) (Stoddart & Gagnon, 2014).…”
mentioning
confidence: 99%
“…However, the conventional dichromate COD method is not sensitive enough to measure COD in surface water (Rittman & Huck, 1989;Stoddart & Gagnon, 2014). Advancements in sensor development for the determination of COD in water have allowed researchers to rapidly quantify COD during drinking water treatment using photoelectrochemical chemical oxygen demand (peCOD) (Stoddart & Gagnon, 2014). When applied in a full-scale biofiltration drinking water treatment plant, peCOD removal was greater than TOC/DOC removal (Stoddart & Gagnon, 2014), which indicated peCOD might be more sensitive than TOC/DOC analysis for understanding biological treatment performance.…”
mentioning
confidence: 99%